Wyrok ostateczny (III Instancji) Trybunału Metropolitalnego w Katowicach (c. Sobański) z 30.04.2004 r. w sprawie o nieważność małżeństwa z tytułu niezdolności psychicznej pozwanej do podjęcia i wypełnienia istotnych obowiązków małżeńskich (kan.1095, n.3) - Grzęźlikowski, Janusz (Ius Matrimoniale, 2005)
The cause about invalid matrimony N. N. to examine three instances: The Bishop Court in Włocławek (I Instance), The Metropolitan Tribunal in Gniezno (II Instance) and on the ground of decree The Highest Tribunal Apostolic Signature The Metropolitan Court in Katowice (III Instance). The cause was conducted through two instances from title the simulation of matrimony agreement defendant (can. 1101, 1), where verdict was decided validity matrimony while from title not capable defendant of assuming the essential obligations of matrimony due to causes of a psychic nature (can. 1095 n. 3) pass through three instances. In Court of Włocławek verdict was decided validity of matrimony, which lever The Court of Gniezno II Instance state invalidity matrimony from title not capable defendant to causes of a psychic nature. The Tribunal of Katowice III Instance declare for validity matrimony confirm the verdict The Bishop Court of Włocławek. This verdict become worthy represent its decisive significant contribution to evolution The Polish jurisdiction in subject not capable of assuming the essential obligation of matrimony due to causes of a psychic nature. This verdict include the instructions of Apostolic Capital in range of decide causes from title can. 1095 n. 3 The Code of Canon Law.